ANALISIS OF ECONOMIC STRUCTURE OF REGENCIES IN ACEH PROVINCE (A CASE STUDY IN BANDA ACEH, SABANG, AND ACEH BESAR) - Syechalad, Mohd. Nur; Bahlia, Muda (Universitas Hayam Wuruk Perbanas, 2010)
This study aims at determining the potential economic growth zones: Banda Aceh city, Sabang, and Aceh Besar regencies in Aceh province. The economic structure concerns regional and interregional specialization in the period of 2000 to 2006. This study combines two research approaches both qualitative and quantitative e.g., shift-share and regional specialization. The data used are in the form of secondary data and are taken from the Central Beauro of Statistics and Regional Government Board at the province and regencies or cities. The results of the shift-share analysis are on regional growth average of the three areas. They are positive with the highest value of Aceh Besar regency and the lowest at Sabang. For the real impact of regional economic growth, the shift-share value is positive during the observation period. Specialization index calculation results indicate a decrease in the average value of specialization indexes between regencies and cities in this region, namely from 0.065 to 0.478 in 2000 to 0.413 in 2006. Among the areas within the region it should take advantage of the excellent potential sectors in the region when trading among the three regions that have the strength in different commodities.